Operational dashboard: Accelerator for shop floor workers - M. M. Yusof, E; S. Othman, M; M. Yusof, R. (International Journal of Engineering and Technology, 2018)
Executing job tasks faster is essential for employees working in the operation section of manufacturing organizations nowadays in order to achieve target profit and gain customer satisfaction. Thus, having a tool to assist them in performing their work faster is necessary. Existing IT system does exist to supply the data they need. However, the entire process is invisible because there is no real-time information available. This causes delay in decisions that they need to make for the operation of the section. To address these issues, this paper presents the Operational Dashboard (OD) for the workers in the operation section of the manufacturing firm. The workersâ€™ needs were first identified to ensure that a right dashboard is being constructed, which is the OD. The OD system was then implemented in the manufacturing firm following the usersâ€™ requirements. The implementation of the OD had shown its effectiveness in shortening the time of the data analysis by the employees in the section. This eventually led to improvement in the decision making process in such a way that the process was done faster as compared to the previous practice.Â Â